Secondary Metabolites from Melocanna baccifera (Roxb.) - Kuddus, M.R.; Rumi, F.; Kaisar, M.A.; Rahman, M.S.; Hasan, C.M.; Hassan, M.A.; Rashid, M.A. (Asian Journal of Chemistry, 2010)
A total of 6 compounds were isolated from the carbon tetrachloride soluble fraction of a methanol extract of the fruits of Melocanna baccifera. The structures of the isolated compounds were elucidated as isochavicinic acid (1), olean-12-en-28-carboxy-3b-acetate (2), 3-oxo-olean-12- en-28-al (3), eugenol (4), b-sitosterol glucoside (5a) and stigmasterol glucoside (5b) by high field NMR (1H NMR and 13C NMR, DEPT, 1H-1H COSY, HSQC and HMBC) analyses as well as by comparison with structurally related compounds.